2008
DOI: 10.1016/j.molcel.2007.10.036
|View full text |Cite
|
Sign up to set email alerts
|

β Clamp Directs Localization of Mismatch Repair in Bacillus subtilis

Abstract: MutS homologs function in several cellular pathways including mismatch repair (MMR), the process by which mismatches introduced during DNA replication are corrected. We demonstrate that the C terminus of Bacillus subtilis MutS is necessary for an interaction with beta clamp. This interaction is required for MutS-GFP focus formation in response to mismatches. Reciprocally, we show that a mutant of the beta clamp causes elevated mutation frequencies and is reduced for MutS-GFP focus formation. MutS mutants defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
173
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(180 citation statements)
references
References 58 publications
7
173
0
Order By: Relevance
“…Several lines of evidence show that mismatch repair proteins assemble into complexes at the site of DNA synthesis (181,384,391). Many replication proteins localize in cells as discrete foci marking the site of DNA synthesis (21,22,99,203,256).…”
Section: Mismatch Repair Proteins Are Coupled To Dna Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence show that mismatch repair proteins assemble into complexes at the site of DNA synthesis (181,384,391). Many replication proteins localize in cells as discrete foci marking the site of DNA synthesis (21,22,99,203,256).…”
Section: Mismatch Repair Proteins Are Coupled To Dna Synthesismentioning
confidence: 99%
“…Many replication proteins localize in cells as discrete foci marking the site of DNA synthesis (21,22,99,203,256). Some of the first evidence suggesting that mismatch repair is coupled to DNA synthesis came from visualizing the formation of mismatch repair foci in human cell culture and in live B. subtilis cells (181,384,391). In B. subtilis, MutS-GFP and MutL-GFP fusion alleles expressed from their native promoter were shown to form foci in a small proportion of cells (ϳ5 to 10% of cells) during exponential-phase growth, and this proportion was increased when cells were challenged with the mismatch-forming agent 2-aminopurine (2-AP) (384,391).…”
Section: Mismatch Repair Proteins Are Coupled To Dna Synthesismentioning
confidence: 99%
“…The mutation frequencies were largely comparable between strains MK244 and MK633, although G. kaustophilus MK633 lacked the gkp08 gene responsible for dam-like methylation (5′-GG 6m ATC-3′and 5′-G 6m ATCC-3′) and the dam methylation (5′-G 6m ATC-3′) is essential for DNA mismatch repair in E. coli [29]. In B. subtilis 168, DNA mismatch repair only involves mutS and mutL products, which do not depend on DNA methylation [30,31], thereby suggesting that G. kaustophilus may use a mismatch repair system similar to the B. subtilis system rather than the E. coli system. In fact, the G. kaustophilus genome [17] contains mutS and mutL but not mutH, as found in B. subtilis 168.…”
Section: Discussionmentioning
confidence: 97%
“…Bacterial MutS and MutL interact with the β-processivity clamp protein, suggesting they may associate with the replication fork (7)(8)(9). Earlier efforts by the Walker and Grossman laboratories (9,10) to localize MutS in live B. subtilis cells exploited a MutS-green fluorescent protein fusion (MutS-GFP).…”
mentioning
confidence: 99%
“…Earlier efforts by the Walker and Grossman laboratories (9,10) to localize MutS in live B. subtilis cells exploited a MutS-green fluorescent protein fusion (MutS-GFP). Although this work supports the idea that MMR is replication coupled, recent work demonstrated that only ∼10% of cells display detectable MutS-GFP foci, with only approximately one-half of these colocalizing with the replication fork (11).…”
mentioning
confidence: 99%